Gas Chromatographic, and Molecular Statistical Study of the Cluster Adsorption of Water and Methanol Molecules onto Lyophilic Centres on a Generally Lyophobic Adsorbent Surface - Yuri I. Tarasevich; Eugene V. Aksenenko; Albina I. Zhukova; Svitlana V. Bondarenko (Adsorption Science & Technology)
A comprehensive theoretical and experimental study of the adsorption of water and methanol molecules onto the active centres (carboxy and phenol groups) of a graphitised carbon black surface is reported. It was shown that the micro-clusters formed during the adsorption process possess a cyclic structure involving four to five molecules, similar to that found earlier in liquid water and at the silver iodide surface. Analysis of the structure and energetics of these clusters showed that their formation is governed primarily by the formation of hydrogen bonds, whilst energetic effects related to the change in the state of motion of the molecules during their adsorption also play a certain role. It was shown that the generalised Langmuir equation derived from molecular statistical considerations is capable of providing a good description of the experimental isotherm over a wide surface coverage range. It also provides a consistent interpretation of the data on the structural and energetic characteristics of the adsorption systems studied as obtained by gas chromatographic and quantum chemical methods.